2022
DOI: 10.3390/jcm11113191
|View full text |Cite
|
Sign up to set email alerts
|

Hand Washing: When Ritual Behavior Protects! Obsessive–Compulsive Symptoms in Young People during the COVID-19 Pandemic: A Narrative Review

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic had a profound impact on the lifestyles and mental health of young people. It has been hypothesized that the focus on hygiene and the fear of contamination/infection during the pandemic may have exacerbated obsessive–compulsive (OC) symptoms in this population. OC symptoms are widespread in the general population, with varying degrees of intensity. At their most extreme, they manifest in obsessive–compulsive disorder (OCD), which is characterized by obsessive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
0
5
0
1
Order By: Relevance
“…The washing-contamination subgroup is expected to experience a greater fear of infection by a virus [ 23 ]. Although a study showed that there was no difference between different OCD subgroups in terms of anxiety and depression symptoms, and no significant difference was observed between healthy controls and OCD patients [ 51 ], a narrative review of studies indicated that obsessive-compulsive symptoms, especially hand washing, increased during the pandemic [ 60 ]. Further studies in the future can provide valuable information about the anxiety response pattern of OCD patients and its subtypes in the face of a global health crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The washing-contamination subgroup is expected to experience a greater fear of infection by a virus [ 23 ]. Although a study showed that there was no difference between different OCD subgroups in terms of anxiety and depression symptoms, and no significant difference was observed between healthy controls and OCD patients [ 51 ], a narrative review of studies indicated that obsessive-compulsive symptoms, especially hand washing, increased during the pandemic [ 60 ]. Further studies in the future can provide valuable information about the anxiety response pattern of OCD patients and its subtypes in the face of a global health crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 fear parameters include the individual behavioral issues that are followed by individuals to restrict the spread of the virus. Fear factors include frequent pandemic-related news updates, frequent hand washing, limiting access to family members, postponing regular medical check-ups, and so on (Demaria et al, 2022). It is evident from earlier literature that during times of crisis, people who are very fearful and cautious may develop depressive symptoms when extreme restrictions are imposed (Barbisch et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…(10) Recientemente se ha implicado al estrés como un factor contribuyente en la etiopatogenia de la dermatitis de manos, situación similar que ocurre con el exceso de lavado de manos. (11) Se evidenció en nuestro caso que la mayoría de los profesionales de salud que hacen uso de guantes de látex con talco y una cifra relativa correspondía a aquellos que usan este mismo tipo de guantes sin talco.…”
Section: Discussionunclassified